LONG-TERM CHANGES IN RELATIVE HUMIDITY AND SOIL WETNESS: IMPLICATIONS ON AGRICULTURE AND ENVIRONMENTAL SUSTAINABILITY IN WESTERN HIMALAYA - Ashwani, Ashwani; Kumar, Pankaj (Journal of Environmental Science and Sustainable Development, 2026)
Long-term climate changes in humidity and soil wetness in the cold deserts of the Western Himalaya are still not well researched. Understanding the long-term trends of relative humidity (RH) and soil moisture is crucial in high-altitude, cold desert regions for effective agricultural management and environmental sustainability. The study was conducted in a part of the western Himalaya, which is an ecologically fragile zone with a highly sensitive agricultural region that is vulnerable to climatic variations. A comprehensive study was conducted to evaluate the spatiotemporal variability of RH and soil wetness by means four techniques: Mann-Kendall, Modified Mann-Kendall, Sen’s slope estimator, and innovative trend analysis. All this was done using NASA POWER climate data from 1981 to 2023. High RW and soil wetness levels were observed in all seasons, with a statistical significance obtained through the Z-values: 12.64 for RH and 9.91 for soil wetness. The monsoon and agricultural seasons were the most intense periods of development. The strongest upward trends were observed in the southern and central subregions. The slopes of Sen showed an annual rise of the RH of 0.31% per year and of the soil moisture of 0.0073 m³/m³/year. The results show significant changes in agriculture and its sustainability. The introduction of new disease-resistant and short-duration crop varieties, the implementation of precision irrigation based on real-time soil moisture data, and adoption of agro-climatic advisories tailored to seasonal fluctuations. However, combining these hydro-climatic patterns with regional climate-smart agriculture strategies, improving monitoring infrastructure, and reinforcing early warning and insurance systems are crucial methods for planning climate-resilient policies in cold desert agro-ecosystems.